Structure-Based Virtual Screening to Identify Novel Potential Compound as an Alternative to Remdesivir to Overcome the RdRp Protein Mutations in SARS-CoV-2 - Kumar D, Thirumal; Shaikh, Nishaat; Kumar S, Udhaya; Doss C, George Priya; Zayed, Hatem (Frontiers in Molecular Biosciences, 2021)
The number of infected cases of and deaths due to SARS-CoV-2 are rapidly increasing with the development of this disease into a pandemic, treatment is being sought worldwide. Few promising drugs, such as Remdesivir, Chloroquine, Hydroxychloroquine, Lopinavir and Ritonavir, are being tested against SARS-CoV-2 as a drug repurposing approach. Remdesivir is the drug of choice for Ebola virus disease and has been authorized for emergency use in the United States and Japan for people exhibiting severe symptoms. This drug acts against SARS-CoV-2 by inhibiting the RNA-dependent-RNA-polymerase (RdRp) of SARS-CoV-2. RdRps of the viruses are prone to mutations that confer drug resistance. A recent study by Pachetti et al. in 2020 identified the P323L mutation in the RdRp protein of SARS-CoV-2. In this study, we aimed to determine the potency of lead compounds similar to Remdesivir, which can be used as an alternative when SARS-CoV-2 develops resistance due to RdRp mutations. The initial screening fetched 704 compounds that were 90% similar to the control drug, Remdesivir. On further evaluation through drugability and antiviral inhibition percentage analyses, we shortlisted 32 and 7 compounds, respectively. These seven compounds were further analyzed for their molecular interactions, which revealed that all seven compounds interacted with RdRp with higher affinity than Remdesivir under native conditions. However, three compounds failed to interact with the mutant protein with higher affinity than Remdesivir. Furthermore, the compound SCHEMBL20144212 showed high affinity for both native and mutant proteins and can be an alternative in case of Remdesivir failure. Further validations by in vitro and in vivo studies are needed to confirm the efficacy of the lead compound.